PENERAPAN METODE SIMULASI TENTANG PERKEMBANGBIAKAN VEGETATIF BUATAN DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DI MADRASAH IBTIDAIYAH PANGERAN AJI KABUPATEN OKU TIMUR - Irham Falahuddin; Melisa Agustin (Universitas Islam Negeri Raden Fatah Palembang, 2013)
Simulation method is a method of learning that can create a conducive learning atmosphere. The learning method is an important factor in improving student's learning outcomes for all subjects, particularly on the subjects of Natural Sciences (IPA). The use of methods that do not comply with the purpose of teaching would be an obstacle in achieving the goal. Therefore, this study looked at and determined whether there was an influence between the applications of simulation methods to the learning outcomes of students in science subjects of artificial vegetative propagation in MI Pangeran Aji East OKU. Besides. The study was also aimed at finding out whether those factors support or inhibit the application of simulation methods of artificial vegetative propagation in improving student learning outcomes in science subjects in MI Pangeran Aji East OKU. This study used an experimental method, with data analysis by using product moment correlation. The final conclusion is that there was a significant relationship between the application of simulation methods to the learning outcomes of students in science subjects of artificial vegetative propagation as seen in the result where rt is smaller than ro;  0.374 < 0.832 > 0.478 . By its antecedents, which does not require a large fee, students interest in learning was more increased. Moreover, teachers could assess the interaction of learning in groups. Whereas, the inhibiting factor was the high motivation of the students to make students communicate with friends so that they can exchange knowledge, the time required seemed slightly.